SIKAP PESERTA DIDIK DALAM MENGIKUTI PELAJARAN IPS TERPADU STUDI PADA SMP NEGERI 1 SUNGAI TARAB (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2016)
The attitude of the students in learning is one of the factors which influence the learning process, and very influential in the results obtained learners. Each learner has different characteristics. This study aims to determine the readiness of the students will go to school, at the motivation of learners in a lesson in school, as well as the completeness of the equipment brought to school learners. This type of research used in this research is descriptive with quantitative approach. The results obtained on the readiness of going to school learners in SMP Negeri 1 Sungai Tarab in the category quite well with the result of 78.73%. Motivation to absorb the lessons of the learners in SMP Negeri 1 Tarab River that are in good enough category that is equal to 72.09%. Completeness of the equipment brought to school learners in SMP Negeri 1 Tarab River that are in good enough category that is equal to 73.08%. Keywords: attitude, readiness, motivation, Fittings